KONTRIBUSI RETRIBUSI PASAR TERHADAP PENDAPATAN ASLI DAERAH KOTA SAMARINDA - -, Hardis Muhammad (EKONOMIA, 2015)
The problem in this study is whether there are differences in the contribution levy market before and during regional autonomy on revenue of City of Samarinda, while the purpose of this study to determine and levy contributions market menganalsis difference before and during the autonomy of the Local Revenue Samarinda.Basic theory used to finance particularly financial management area, Levies and Local Revenue. The hypothesis of this study there was no significant difference Contributions Levy Market before and during the Regional Autonomy of the Local Revenue Samarinda.Analysis used by the difference test using data for 1996/1997 - 2000 and 2007-2011. Based on the analysis and discussion, the conclusion of this study:Growth Market levy revenue Samarinda before and during the regional autonomy has fluctuated from year to year. Comparison between the average contribution to the Market Market Reribusi revenue (PAD) Samarinda before the autonomy of 3.2% compared with the Regional Reribusi Market to revenue (PAD) Samarinda during the autonomy 3.87%, it appears that the contribution before decentralization is smaller than the contribution after regional autonomy (3.2% <3.87%), this is due to revenue (PAD) Samarinda still bertumpuh on Market Reribusi during regional autonomy.Value of average annual contribution Reribusi contribution to the Market Market Revenue (PAD) Regional Samarinda before decentralization of Rp 754 million, while the value of the average contribution per year contribution to the market Reribusi revenue (PAD) Samarinda City during regional autonomy Rp 2,018 million this means that the average annual contribution Reribusi contribution to the Market Revenue (PAD) Samarinda before regional autonomy is not the same as the average contribution per year contribution to the market Reribusi revenue (PAD) Samarinda City during regional autonomy. Furthermore, when seen from the t value of -165 is smaller than t table at n-2 with a 95% confidence level = - 3.182, this means that t <t table, these results suggest that there are significant differences in the contribution Reribusi Market before autonomy daeerah period 1995 / 1996-1999 / 2000 and during the 2007-2011 period of regional autonomy to revenue (PAD) Samarinda, the research hypothesis is accepted